Observing soil organic carbon spatial and seasonal variability at the Golan Heights using Rock-Eval measurements - Weiner, Tal; Rosenberg Oved, Yoav; Angert, Alon (PANGAEA, 2025)
Soil organic matter (SOM) stores most of the terrestrial carbon, and changes in this storage can have a significant effect on the global carbon cycle. Various approaches have been used to understand the SOM transformations and stability. Here, we estimated the long-term SOM stability, and the effect of decomposition on the stability and composition of the remaining fraction, by Rock-Eval pyrolysis. The sampling took place in Mount Baron, the Golan Heights, in October 2021, February 2022, and June 2022, which represent the beginning, middle, and end of the rainy season. . Each sample was pooled from 2 locations and taken by a trowel from A-horizon at 0-10 cm depth.. At each campaign, the soil was sampled at 4 heights along the north and south slopes, under tree canopy, and in open grassland. In addition, to study the different fractions of organic matter, we analyzed soil separated into particulate organic matter (POM) and mineral-associated organic matter (MAOM). The samples were dried to 55°C and were ground with a mortar and pestle before the Rock-Eval analysis (Rock Eval 6, Vinci Technologies, at Ben Gurion University of the Negev for October samples and Rock Eval 7S, Vinci Technologies, at the Geological Survey of Israel for February and June samples).
Keywords: soil carbon; Soil carbon efflux; Soil Organic Carbon (SOC); soil organic matter